Model Pembelajaran IPS yang Menggunakan Unsur-Unsur Penting Kehidupan Nyata Masyarakat Sebagai Sumber Belajar - Dedi Kuswandi (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2016)
The purpose of this research is to reveal and describe the efforts made by elementary teachers in designing, developing and implementing social studies learning that uses elements of the interests of community life as a learning resource. A qualitative approach with observation and interview techniques was used as a data collection tool. The results showed the findings that the use of real-life elements of society can improve students 'critical thinking skills, mastery of social studies learning materials, and can develop students' habituation, morals and self-confidence.